The Role of Neuropeptide Y in Cardiovascular Health and Disease - Tan, Cheryl M. J.; Green, Peregrine; Tapoulal, Nidi; Lewandowski, Adam J.; Leeson, Paul; Herring, Neil (Frontiers in Physiology, 2018)
Neuropeptide Y (NPY) is an abundant sympathetic co-transmitter, widely found in the central and peripheral nervous systems and with diverse roles in multiple physiological processes. In the cardiovascular system it is found in neurons supplying the vasculature, cardiomyocytes and endocardium, and is involved in physiological processes including vasoconstriction, cardiac remodeling, and angiogenesis. It is increasingly also implicated in cardiovascular disease pathogenesis, including hypertension, atherosclerosis, ischemia/infarction, arrhythmia, and heart failure. This review will focus on the physiological and pathogenic role of NPY in the cardiovascular system. After summarizing the NPY receptors which predominantly mediate cardiovascular actions, along with their signaling pathways, individual disease processes will be considered. A thorough understanding of these roles may allow therapeutic targeting of NPY and its receptors.